(untitled) (Eurasian Journal of Ecology, 2016)
Active strains – destructors of hydrocarbons isolated from the root zone of plants grown in oil contaminated soil. 20 strains belonging to different Pseudomonas, Rhodococcus, Microbacterium, Gordonia and Bacillus genera are able to utilize oil and fuel oil.